2002
DOI: 10.1136/bjo.86.8.892
|View full text |Cite
|
Sign up to set email alerts
|

Polypoidal choroidal vasculopathy in Chinese patients

Abstract: Aims: To report the clinical features and outcomes of polypoidal choroidal vasculopathy (PCV) in Chinese patients with or without laser treatment. Methods: A consecutive series of 204 indocyanine green angiographies (ICGA) performed for patients with a provisional diagnosis of age related macular degeneration were reviewed retrospectively. Inclusion criteria were ICGA with angiographic features of PCV and patients of Chinese ethnic origin. Medical records were then reviewed and patients were recalled for furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
112
4
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 16 publications
8
112
4
4
Order By: Relevance
“…[11][12][13] This is in contrast to other series with predominantly Caucasian populations in which 15-47% were men. 14,15 It has been reported that 36% (5/14) of eyes with PCV and not treated had a worsening of visual acuity by 42 lines after a follow-up period of at least 2 years.…”
Section: Discussionmentioning
confidence: 84%
“…[11][12][13] This is in contrast to other series with predominantly Caucasian populations in which 15-47% were men. 14,15 It has been reported that 36% (5/14) of eyes with PCV and not treated had a worsening of visual acuity by 42 lines after a follow-up period of at least 2 years.…”
Section: Discussionmentioning
confidence: 84%
“…While in the past, some reports exclusively associated PCV with old black females patients, [1][2][3]5 recently it has also been identified in male patients, other races, and ethnic groups. 8,9,11,12,14,15 Curiously in Japanese and Chinese patients, PCV is evident more prevalent in men. 8,15 In our series of white Greek patients, the difference in sex prevalence between PCV and AMD was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,11,12,14,15 Curiously in Japanese and Chinese patients, PCV is evident more prevalent in men. 8,15 In our series of white Greek patients, the difference in sex prevalence between PCV and AMD was not statistically significant. Further, the frequency of PCV was almost the same in both sexes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations